(untitled) (Research, Society and Development, 2023)
Objective: to evaluate the preoperative characteristics that predict a complex videolaparoscopic cholecystectomy in the surgical procedure. Methodology: descriptive retrospective observational study through data collection from medical records of patients undergoing cholecystectomy at FSCMPA, which were analyzed through expository tables using Microsoft Word® and Microsoft Excel®. All statistical tests were performed using the Bioestat 5.5 software. Results: There were 114 females in the population (79.2%) and 30 males (20.8%). The most prevalent age group was 30 to 59 years old, with 100 attendances (69.4%). The mean age was 47.59 years. The highest frequency of admission of patients for surgery was elective, constituting 97.2% (140) of cases. Biliary colic was the most prevalent clinical finding and constituted 74.3% (107). The second most prevalent was the presence of cholecystitis 17.4% (25). In the final risk classification, the most prevalent was the score from 0-3, with 75% (108). The chances of having an altered bile duct is 11 times greater in participants at high risk. Conclusion: The results are relevant for the identification of possible predictive preoperative variables, which can contribute to improving the quality of patient care and health management planning.